Evaluation of cutting temperature of a tool with a curved cutting edge - Moiseev Denis; Ryzhkin Anatoliy; Volokitin Gennadiy (MATEC Web of Conferences, 2017)
A model for solving the problem of heat distribution along the front surface of a tool with a shaped profile is considered. Analytical dependencies for estimating the temperature of the tool of elliptic profile for turning with radial feed in Cartesian and polar coordinate systems are obtained for the model under consideration. As a result, the obtained dependences can be applied to similar thermal calculations of instruments with other forms of plane curves both in turning with radial feed and in milling conditions. The calculation of a flat temperature field on the front surface of a shaped tool has been carried out and it has revealed areas with the highest temperatures at the contact area and the maximum wear values.